Use of coated silicon field emitters as neutralisers for fundamental physics space missions - Aplin, K; Kent, B; Collingwood, C; Wang, L; Stevens, R; Huq, SE; Malik, A (2011)
Spacecraft neutralisers are required as part of the ion propulsion system for accurate station keeping in fundamental physics missions. This paper describes the use of thin layers of insulating materials as coatings for the gated silicon field emitter array structure used in a spacecraft neutraliser. These thin coatings are postulated to reduce power consumption and reduce overheating. The power consumption and lifetime of aluminium nitride and amorphous hydrogenated diamond-like carbon coatings have been tested by current-voltage and endurance tests. Diamond-like carbon coatings were promising, performing better in endurance tests than uncoated samples, but further work is required to characterise the coating's physical properties and its effects on field emission. The thermal conductivity of the coating material had little effect on measured sample lifetimes. Aluminium nitride had reduced power consumption compared to diamond-like carbon coated and uncoated samples. A thin (∼5 nm) layer of aluminium nitride was found to be optimal, meeting European Space Agency specifications for the neutraliser engineering model. © 2011 COSPAR. Published by Elsevier Ltd. All rights reserved.